EVALUASI PENDIDIKAN ISLAM PERSPEKTIF HADIS - Muhammad Zein Damanik; Dini Yuliani; Dwi Ananta Aura Ningrum; Dea Novita (Jurnal Al Wahyu, 2023)
The purpose of this study is to describe how education in the Hadith is evaluated in one of the studies that employs a case study methodology in conjunction with literature review research. The purpose of this work is to explain the idea of educational evaluation from a Hadith perspective. details regarding the outcomes and calculate the value based on the information. Every action should be evaluated since it is via evaluation that the worth of the work done may be ascertained using the data collected. Islam sees education as having components, purposes, and goals that must all be met in order to be evaluated. Excellent comprehension of the subject matter, behavioral development, and student insights and habits as benchmarks for next year's educational improvements.